EFEKTIFITAS PENGGUNAAN MEDIA ULAR TANGGA UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK MATERI SUHU - Dina Yulinar; Edy Tandililing; Diah Mahmuda (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2019)
AbstractThis study aimed to find out the differences between student learning outcomes before and after by using the snakes and ladders game as a media in the temperature material in class VII Darut Tauhid Sungai Sungai Raya School and to find out the effect size of student learning outcomes before and after using snakes and ladders game as a media in temperature material in class VII SMP Darut Tauhid Sungai Raya. The research method used was a quantitative method (experiment). The type of research used was Pre-Experimental with the design of One-Group-Pretest-Posttest-Design. The sample of this study was students of class VII B.  Based on the results of data analysis, the difference in average learning outcomes scores from 40.43 to 72.21 or with a difference in the average score of 31.78, as well as the specifications obtained from the increase in students learning outcomes worth 0.53 with a moderate category tested using n-gain test. It  indicated  that the effect size of before and after using the snakes and ladders game as a media in this study has an effect of 48.61% to improve student learning outcomes after using snakes and ladders game as a media on temperature material.Keywords: Learning Outcome , Snakes  Ladders Game